Analisis Studi Literatur Tantangan Penerapan Flexible Working - Noor Ritawaty; Siti Umairah; Khoirul Hadziq; Fredy Sitorus; Septa Efraim Tarigan (Syntax Corporation Indonesia, 2024)
In the current digital era, the concept of flexible work has become increasingly relevant and pressing. The COVID-19 pandemic that swept the world has accelerated the adoption of flexible work practices, with many organizations forced to adapt to new situations where working from home has become the norm. However, the implementation of flexible work does not always proceed smoothly and presents various challenges, such as cultural and organizational changes, effective performance management, and equality of access and technology. This research analyzes the challenges and inhibiting factors in implementing flexible work based on previous literature studies. These challenges include cultural and organizational changes, performance management and supervision, equality of access and technology, work-life balance, conflict management and communication, as well as variations in the effects of flexible work on job quality. Inhibiting factors include difficulties in assessing individual readiness, technical challenges and infrastructure, competency gaps and technological limitations, as well as managerial difficulties. To address these challenges and inhibiting factors, organizations need to take appropriate steps, including policy adjustments, providing training and technology support, and developing appropriate performance management systems.